Panggilan Pelayanan sebagai Penguatan Identitas dan Profesionalisme Guru Sekolah Agape di Sumberejo: - - Daniel de Queldjoe; Kheren Yuniarti; Gery Adam Datutasik; Ameylia Puan Kristania; Perwira Bintang; Sefanya Prischa Dyah Rahmadani; Sri Suwartiningsih (Universitas Kristen Satya Wacana Salatiga, 2026)
This community service research was motivated by the importance of strengthening the identity and professionalism of early childhood and kindergarten teachers at Agape Sumberejo School, especially amid limited facilities, teaching staff, and material rewards. This activity aims to strengthen the meaning of the call to service as a moral and motivational foundation in early childhood education practices. The method used is descriptive qualitative through field studies based on experiential learning, with participatory observation techniques, semi-structured interviews, and documentation of teachers, church administrators, and congregations. The analysis was conducted thematically with triangulation of sources and techniques. The results of the service showed that the internalization of the calling to serve was able to increase the commitment, professional resilience, and pedagogical consistency of teachers. The integration of professionalism and service values formed the identity of teachers who are ethical, relational, and oriented towards the continuous development of children's character.